2018
DOI: 10.1590/1678-6971/eramg180021
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness and Theory U for the Professional Sense of Purpose

Abstract: Purpose: To validate if mindfulness practices contribute to increase the perception of clarity of the own professional sense of purpose. Originality/value: The research shows synergy of mindfulness practices with metacognitive reflections based on Otto Scharmer’s Theory U attention modes, increasing the perception of authenticity in the statements defining the own professional sense of purpose. Design/methodology/approach: This is an exploratory, prospective intervention study, with pre and post-intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…We found that utilizing U-theory to explore novel strategies for building new mental models resulted in increased perceptions of clarity, focus, and authenticity. These outcomes are highly relevant to the personal statements of teachers and principals who aspire to professional growth (Calia et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…We found that utilizing U-theory to explore novel strategies for building new mental models resulted in increased perceptions of clarity, focus, and authenticity. These outcomes are highly relevant to the personal statements of teachers and principals who aspire to professional growth (Calia et al, 2018).…”
Section: Resultsmentioning
confidence: 99%